An A-Z of creative teaching in higher education - Ashton, Sylvia; Stone, Rachel (College teacher) (Los Angeles SAGE, 2018)
"This is a rich source of innovative approaches to learning and teaching in HE. It addresses some common issues faced by lecturers, and includes case studies and practical suggestions for teaching. The text takes a critical approach to exploring themes from different perspectives and highlights important and recent theory in the field. Chapters cover themes such as creating enabling learning environments, supporting students to learn constructively in large groups, working with international learners, embedding employability skills and developing self-directed (or 'flipped') learning resources. Each section has practical examples from a range of subject disciplines along with links to further reading. This is an essential guide to teaching and learning for new and experienced practitioners in higher education, those seeking professional accreditation and those wanting to improve the experience of students."--Publisher's website.
N is for No One Excluded. -- Z is for Zzzzzzz. -- Y is for Why. -- X is for Expectations. -- W is for Wellbeing. -- V is for Visuals. -- U is for Understanding. -- T is for Tales. -- S is for Skillful. -- R is for Room. -- Q is for Quiet. -- P is for Presentation. -- O is for Occupations. -- A is for Action. -- M is for Metalearning. -- L is for Listening. -- K is for Knowledge. -- J is for Joy. -- I is for Internationalisation. -- H is for Whole. -- G is for Groups. -- F is for Flexible. -- E is for Emotion. -- D is for Design. -- C is for Communication. -- B is for Blue Skies.
Includes bibliographical references (pages 196-214) and index.
Keywords: College teaching -- Handbooks, manuals, etc; Creative ability -- Handbooks, manuals, etc; College teaching; Creative ability